2010
DOI: 10.4161/cbt.9.6.10893
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies directed to α6β4 highlight the adhesive and signaling functions of the integrin in breast cancer cell lines

Abstract: Integrin alpha6beta4 signaling interactions have been implicated in tumor progression, and beta4 expression has been linked to poor prognosis in certain breast cancer subtypes. We generated human antibodies to alpha6beta4 to further evaluate its role in tumor cell signaling. Biochemical characterization indicated these antibodies are specific for alpha6beta4, recognize distinct epitopes and have low nanomolar affinities for both human and murine protein. The antibodies demonstrated differing effects on alpha6b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
2
0
2
Order By: Relevance
“…It www.nature.com/scientificreports/ is possible that the high level of Akt phosphorylation in A431 cells precluded detection of a subtle effect of β4 on Akt phosphorylation. In line with this reasoning, previous reports have shown that β4 does influence PI3K signaling, but that the effect of β4 on PI3K signaling is diminished by the presence of constitutively active Akt 53,54 . However, in HaCat keratinocytes that do not exhibit high constitutive levels of phosphorylated Akt and in which the EGFR is not overexpressed, an effect of β4 on the EGFR-mediated phosphorylation of Akt could not be demonstrated.…”
Section: Discussionsupporting
confidence: 69%
“…It www.nature.com/scientificreports/ is possible that the high level of Akt phosphorylation in A431 cells precluded detection of a subtle effect of β4 on Akt phosphorylation. In line with this reasoning, previous reports have shown that β4 does influence PI3K signaling, but that the effect of β4 on PI3K signaling is diminished by the presence of constitutively active Akt 53,54 . However, in HaCat keratinocytes that do not exhibit high constitutive levels of phosphorylated Akt and in which the EGFR is not overexpressed, an effect of β4 on the EGFR-mediated phosphorylation of Akt could not be demonstrated.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, the inhibition of signaling pathways to interrupt tumor growth by α 6 β 4 antibody in conjunction with growth factor receptor-targeted therapies is attracting attention. 38 Altogether, α 6 β 4 is a good target and the molecular probes that associate to this target should be attractive and promising theranostic agents.…”
Section: Discussionmentioning
confidence: 99%
“…The α6β4 integrin appears to have importance in breast cancer malignancy, as well as in other epithelial carcinomas [12,13,14,16]. There is strong evidence that α6β4 expression is pathologically significant [17].…”
Section: Introductionmentioning
confidence: 99%